PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN VITAMIN MATA BIOVISION PT. INDOFARMA GLOBAL MEDIKA CABANG MEDAN - Alfairi, Basyits Ali; Karneli, Okta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The problem in this study is the percentage of sales target achievement has decreased, and not achieved the company's sales target, this is thought to be influenced by purchasing decisions. The purpose of this study was to determine the product quality and price of purchasing decisions on biovision products distributed by PT. Indofarma Global Medika, Medan branch.. The population in this study were consumers of biovision products in the city of Medan. Samples taken based on the method using the Roscoe guideline in Sugiono on the third point were 39 respondents.Â  Hypothesis testing uses simple linear analysis methods and multiple linear analysis with the results showing that product quality and price have a positive and significant effect on purchasing decisions on biovision products in the city of Medan. With a simple calculation of the coefficient of determination (R2) on purchasing decisions obtained R square value of 0, 429 or 42.9% and the price of the purchase decision obtained R square value of 0, 447 or 44.7% and calculation of determination (R2) multiple product quality and prices for purchasing decisions obtained R square value of 0.546 or 54.6%. This shows that the quality of products and prices have an effect of 54.6% on purchasing decisions on biovision products in Medan, while the remaining 45.5% are influenced by other variables not examined in this study.Key words: Product Quality, Price, Purchase Decision